Dynamics of the Oxygen, Carbon Dioxide, and Water Interaction across the Insect Spiracle - S. M. Simelane; S. Abelman; F. D. Duncan (Abstract and Applied Analysis)
This paper explores the dynamics of respiratory gases interactions which are accompanied by the loss of water through an insect’s spiracle. Here we investigate and analyze this interaction by deriving a system of ordinary differential equations for oxygen, carbon dioxide, and water vapor. The analysis is carried out in continuous time. The purpose of the research is to determine bounds for the gas volumes and to discuss the complexity and stability of the equilibria. Numerical simulations also demonstrate the dynamics of our model utilizing the new conditions for stability and instability.